Proposta de mapeamento de competências para atuação do trabalhador no contexto da indústria 4.0 - Silva, Leonardo Breno Pessoa da (2021)
The transformations arising from Industry 4.0 are being discussed by scientific, industrial communities and even renowned consultants around the world. Among a relevant aspect of the changes arising from the 4th Industrial Revolution, aspects related to Human Resources 4.0, such as the development of work competence, highlighting scientific attention. Therefore, the present work aims to proportionate the mapping of the important competences for the worker's performance in the context of Industry 4.0. For that, a systematic literature search was carried out, which developed a tool for mapping important competences for the main driving technologies of Industry 4.0. As a methodology for bibliographic survey, PRISMA was used, conducting a systematic review of the literature on Competencies for Industry 4.0 (56 papers), in addition to the consultancy reports used as a source of competences, with content analysis compiled, with the assistance of of the QSR NVIVO [marca registrada] Software version 10, in order to map the Competencies in the literature. These competencies were the basis for the construction of the tool to identify the most important competences based on consultation with specialists, and these data are according to the Relative Importance Index and Cluster Analysis. Based on the bibliographic portfolio, 56 Soft and Hard Skill were cataloged and related to 13 Driving Technologies referenced in the literature. After consultation with specialists, the 10 most important Soft and Hard Skill for each technology analyzed were identified. In addition, a Cluster Analysis was built where the grouping of technologies was configured, according to the competency indices and the behavior of the competencies in each formed group. With this, this study makes it possible to advance with knowledge about the important skills for the worker's performance in the context of Industry 4.0, helping Human Resources 4.0 to publicize the necessary transformations for the workforce based on the specific needs of each driving digital technology. of Industry 4.0.